1999
DOI: 10.1021/bc980140m
|View full text |Cite
|
Sign up to set email alerts
|

A Psoralen-Conjugated Triplex-Forming Oligodeoxyribonucleotide Containing Alternating Methylphosphonate−Phosphodiester Linkages:  Synthesis and Interactions with DNA

Abstract: A psoralen-conjugated oligodeoxyribopyrimidine (1443), PS-pTTTTCTTTTCTTCTT, where PS is trimethylpsoralen and C is 5-methyl-2'-deoxycytidine, that contains alternating methylphosphonate-phosphodiester internucleotide linkages was synthesized. The ability of 1443 to form triple-stranded complexes with a purine tract in a synthetic DNA duplex was studied. Irradiation of solutions containing the DNA target and 10 microM 1443 or 0.25 microM of a similar psoralen-conjugated oligodeoxyribonucleotide that contained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…We find that the methylphosphonate substitution significantly destabilizes the TC triplex, in agreement with previous results (39). The methylphosphonate TFO in the intermolecular system of Lacroix and Mergny (40) did not form a triplex or an i-motif tetraplex.…”
Section: Discussionsupporting
confidence: 92%
“…We find that the methylphosphonate substitution significantly destabilizes the TC triplex, in agreement with previous results (39). The methylphosphonate TFO in the intermolecular system of Lacroix and Mergny (40) did not form a triplex or an i-motif tetraplex.…”
Section: Discussionsupporting
confidence: 92%
“…The chimeric methylphosphonate oligomers were prepared as previously described ( , ). To improve coupling efficiencies, the coupling time was extended to 2 min and an iodine oxidizer containing 0.2% water was used instead of the standard oxidizer that contains 2% water.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions between the oligomers and the enV-DNA target duplex were examined using an electrophoretic mobility-shift assay on nondenaturing polyacrylamide gels. This method is more reliable than UV-melting experiments for assessing binding by the chimeric oligomers because we previously found that oligomers with alternating methylphosphonate/phosphodi-ester linkages give melting curves that have very broad transitions and small hypochromicity changes (52). The target, whose upper strand was 5′-end-labeled with 32 Pphosphate, was incubated at 22 °C overnight prior to electrophoresis with increasing concentrations of oligomer in pH 7.0 buffer containing 2.5 mM magnesium chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoralen-modified oligonucleotides have been used to trap three-stranded RecA-DNA complexes and to study the repair of these cross-linked complexes ( , ). It has also been shown that psoralen-derivatized oligodeoxyribonucleotides and oligoribonucleoside methylphosphonates can specifically cross-link to double-helical DNA and viral mRNA targets, respectively ( , ).
1 Structure of the DNA duplex target and psoTFOs.
…”
mentioning
confidence: 99%